2020
DOI: 10.1128/aem.02568-19
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Biotite and the Mineral-Weathering Bacterium Pseudomonas azotoformans F77

Abstract: In this study, the mineral-weathering bacterium Pseudomonas azotoformans F77, which was isolated from the soil of a debris flow area, was evaluated for its weathering activity under direct contact with biotite or without contact. Then, biotite-weathering behaviors of strain F77, mutants that had been created by deleting the gcd and adh genes (which are involved in gluconic acid metabolism and pilus formation, respectively), and the double mutant F77ΔgcdΔadh were compared. The relative gene expression levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…All these genes (excepted pqqA) showed a significant upregulation in GB than in GBwB but supported by a low expression level. The potential regulation of the PQQ system was reported for some bacterial strains (An and Moe, 2016; Wang et al ., 2020), but other studies suggested that it may be a constitutive mechanism (Zeng et al ., 2017). Concerning the PQQ‐independent enzymes, a total of four GMC oxidoreductases were detected in this study in the genome of strain PML1(12).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…All these genes (excepted pqqA) showed a significant upregulation in GB than in GBwB but supported by a low expression level. The potential regulation of the PQQ system was reported for some bacterial strains (An and Moe, 2016; Wang et al ., 2020), but other studies suggested that it may be a constitutive mechanism (Zeng et al ., 2017). Concerning the PQQ‐independent enzymes, a total of four GMC oxidoreductases were detected in this study in the genome of strain PML1(12).…”
Section: Discussionmentioning
confidence: 98%
“…Glucose is usually oxidized in the periplasm to gluconate and partially further oxidized to 2‐ketogluconate (Hanke et al ., 2013). The PQQ‐dependent GDHs are suspected to be key enzymes involved in mineral weathering (Babu‐Khan et al ., 1995; Golstein, 1995; Wang et al ., 2020). The genome of strain PML1(12) contains several enzymes related to GDH, some pyrroloquinoline quinone (PQQ)‐dependent and some other non‐PQQ dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For details, see Supplementary Methods. In addition, functions associated with siderophore biosynthesis, carbonic anhydrase (CA) [15], agellar assembly [13], and organic acid production [34] were selected as indicators of rock or mineral weathering potentials. Potential differences in the relative abundance of each rockweathering related functional category were also tested with Tukey's HSD post-hoc test.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Membrane-bound metaldependent hydrolase and AAA+-type ATPase are involved in the regulation of metabolism, and have been reported to contribute to metabolic adaptation to physiological host conditions and pathogenicity (Mougous et al, 2006;Parisien et al, 2008;Vermassen et al, 2019;Wyckoff et al, 2012). Furthermore, it has been reported that small RNA binding protein might contribute to virulence controlling (Djapgne et al, 2018;Law et al, 2019;Wang et al, 2020). Interestingly, it has been recently reported that P.…”
Section: Comparative Functional Enrichment Analysis Reveals Host-specmentioning
confidence: 99%